The Tundzha regional archaeology project : surface survey, palaeoecology, and associated studies in central and southeast Bulgaria, 2009-2015 final report - Ross, Shawn A.; Sobotkova, Adela; Tzvetkova, Julia; Nekhrizov, Georgi; Connor, Simon, 1987- (Oxbow Books, 2018)
This volume presents the results of diachronic archaeological and palaeoecological research conducted in two study areas: the intermontane Kazanlak Valley along the Upper Tundzha River of central Bulgaria, and the Thracian Plain along the Middle Tundzha River south of the city of Yambol in southeastern Bulgaria. The Tundzha Regional Archaeology Project (TRAP), a cooperative effort including Australian, Bulgarian, and Czech investigators, undertook archaeological survey and environmental sampling between 2009-2011. Major field activities of the project included over 100 sq km of systematic pedestrian survey, legacy data verification and mapping, trial excavations, artefact processing, and environmental sampling in and around the study areas. Through this research, TRAP inventoried over 100 surface artefact concentrations and 800 burial mounds. At the heart of the volume is a geospatial analysis of settlement patterns derived from the survey dataset, which relates the footprint of past human activities to environmental and sociocultural drivers. We also present a range of associated studies conducted between 2009-2015. Finally, TRAP has produced a granular digital dataset of surface artefacts and features unparalleled in Bulgaria to promote reinterpretation of our results, encourage secondary studies, and foster comparative research.